The Comparison effects of Selected Aerobic Continues and Interval Exercise Program on Heart Rate Recovery of POST CABG Patients - علی اصغر فلاحی; مصطفی نجاتیان; عباسعلی گائینی; محمدرضا کردی (فیزیولوژی ورزش و فعالیت بدنی)
Introduction: The purpose of this study was the investigation effects of selected aerobic continues and noncontinues(interval) exercise program and comparison of this programs on HRR of POST CABG patients.Therefore, thirty three (30 men, 3 women with mean age: 58.33± 9.50 and mean BMI: 27.05±3.55 kg/m2)POST CABG patients were divided to a selected aerobic continues training, 30-60 min and intensity of 70–85% of HR peak (AC, n=12) or an aerobic interval training with three interval (9- 15 min), 27-45 min andintensity of 75-90% of HR peak (AI, n=12 and a control group (C, n=9) three times a week for 8 weeks. Resultshowed, training-induced a positive significant differences in HRR (AC: pre: 13.58±8.45, post: 18.17±5.92,p=0.049), (AI: pre: 14.66±12.16, post: 22.33±8.59, p=0.033) (C: pre: 11.9±4.76, post: 12.50±13.87, p=0.279).In comparison of groups, there are a significant difference between groups after programs (p=0.30). Post hoctest (LSD) showed, there are a significant differences between AI and C groups (p=0.008) but not between AIand AC (p=0.207), and also AC and C groups (0.115). In summary this study indicates both continuous andinterval exercise training program improves HRR in CABG patients, interval rather than continuous exercisetraining improves early HRR1, in men and women with coronary artery bypass graft surgery.